2020
DOI: 10.1038/s41386-020-0604-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating PACAP peptide and PAC1R genotype as possible transdiagnostic biomarkers for anxiety disorders in women: a preliminary study

Abstract: Research in humans implicates PACAP as a useful biomarker for the severity of psychiatric symptoms in response to psychological stressors, and work in rodent models suggests that PACAP manipulation exerts downstream effects on peripheral hormones and behaviors linked to the stress response, providing a potential therapeutic target. Prior work has also suggested a potential sex difference in PACAP effects due to differential estrogen regulation of this pathway. Therefore, we examined serum PACAP and associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…Neuropeptides' role in ADs have been extensively studied in animal and human samples, underlying their role in the pathophysiology of ADs and as promising new targets for treatment interventions [75,76]. The most important neuropeptides that play a role in the modulation of stress-related behaviors and anxiety are cholecystokinin (CCK) [77][78][79], oxytocin (OXT) [80][81][82][83], substance P [84], neuropeptide Y, galanin [76], pituitary adenylate activator polypeptide (PACAP) [85,86], ghrelin [87], and leptin [88].…”
Section: Neuropeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropeptides' role in ADs have been extensively studied in animal and human samples, underlying their role in the pathophysiology of ADs and as promising new targets for treatment interventions [75,76]. The most important neuropeptides that play a role in the modulation of stress-related behaviors and anxiety are cholecystokinin (CCK) [77][78][79], oxytocin (OXT) [80][81][82][83], substance P [84], neuropeptide Y, galanin [76], pituitary adenylate activator polypeptide (PACAP) [85,86], ghrelin [87], and leptin [88].…”
Section: Neuropeptidesmentioning
confidence: 99%
“…Pituitary Adenylate Cyclase-Activating Polypeptide. A study reported female GAD patients, but not male subjects, to be associated with lower levels of circulating PACAP compared with HCs, as well as with worse anxiety somatic symptoms and insomnia when associated with a specific gene polymorphism (PAC1R CC) [86]. This gender difference could be related to an estrogen response element of the PAC1R allele [85].…”
Section: General Anxiety Disordersmentioning
confidence: 99%
“…Of note, the behavioral phenotype of PACAPknockout mice varies under different environmental conditions and different genetic backgrounds (mouse strain), and with the specific gene sequences that were deleted in the different PACAP gene knockout models. In humans, the dysregulation of PACAP and the PAC1 receptor has been associated with schizophrenia, depression, and post-traumatic stress disorder (PTSD) (Hashimoto et al, 2007(Hashimoto et al, , 2010Ressler et al, 2011;Mercer et al, 2016;Ross et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A single-nucleotide polymorphism (SNP) in the adcyap1r1 gene encoding PAC1R is associated with symptom severity in women, but not men; altered DNA methylation of the same gene is associated with PTSD in both sexes ( Ressler et al, 2002 ; Almli et al, 2013 ). The risk allele for PTSD is also associated with symptom severity in GAD females, but not males ( Ross et al, 2020 ). The SNP is located in an estrogen-response element (ERE), and the nucleotide change interferes with estradiol-estrogen receptor alpha binding the ERE, leading to a decrease in receptor expression ( Mercer et al, 2016 ).…”
Section: Sex Differencesmentioning
confidence: 99%